Analysis of Increased Student Autonomy due to Pandemic using Critical Success Factors - Araújo, Nino Ferraz (Cadernos de Educação Tecnologia e Sociedade, 2022)
During this advent of the pandemic, educational institutions need to reinforce the responsibility of transmitting knowledge by promoting student development and, at the same time, reinventing themselves through distance learning. One of the essential factors for students to improve their performance is the increase in their autonomy outside the school environment, which, due to the pandemic, this process has been accelerated. Thus, educational managers must use strategies to develop the school's organizational environment around this purpose. This work aims to contribute with data that corroborate student development outside the school environment, facilitating and even increasing student performance, through the use of Critical Success Factors. These factors involve aspects such as: study discipline, parental support, teaching tools and psychological well-being. The theoretical framework used to treat Rockart's Critical Success Factors (1979) was used as methodology, Kolmogorov-Smirnov (1979). As the Komolgorov-Smirnov method has a simplified application, Paraconsistent Logic will also be used, as it allows for the natural treatment of divergences, inconsistencies and contradictions, in addition to allowing the achievement of more accurate and closer to reality results (Bispo and Cazarini, 2006). It was concluded that both the use and the prioritization of Critical Success Factors (FCS) positively influence student performance outside the classroom and increase their performance. Therefore, it was found that by ordering the Critical Success Factors in a degree of the following importance: 1 - psychological well-being, 2 - parental support, 3 - study discipline and 4 - teaching tools, the students' performance improved. This work is restricted to thirty private elementary and high schools in the city of São Gonçalo, in the State of Rio de Janeiro. This delimitation makes the results obtained subject to standards such as market behavior and requirements. It is also expected, in addition to adding value to the current literature, to stimulate studies around the proposed theme, aiming increasingly to assist students in improving their autonomy. No studies were found in the literature proposing the use of FCS to improve student autonomy during the pandemic. Therefore, this work intends to describe innovative proposals for this segment; give the educational manager a prominent role in the process of increasing student autonomy by identifying and prioritizing FCS; and, finally, to contribute with other works that evaluate the quality of the attendance to the students.